Consumers' intention to use mobile payment : a case of quick response (QR) code applications / Nur Fathin A. Rosli ... [et al.] - Nur Fathin, A. Rosli; Roslina, Ibrahim; Yazriwati, Yahya; Norziha M., M. Zainuddin; Suraya, Yaacob; Rasimah, C. M. Yusoff (UiTM Press, 2020)
Many transactions, nowadays such as banking, transportations, online shopping and bills payments, are implemented using mobile payment. To date, many mobile payment services are available in Malaysia, with companies offering their services competitively. However, adoption rates in Malaysia are considered slow due to many reasons. This study investigates the factors that affect consumer intention to use mobile payment based on QR code technology. A proposed model based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model was adapted to identify the factors that affect the use of mobile payments. A survey instrument was developed based on the proposed model. Data were collected from 50 consumers who used QR code mobile payments in Klang Valley. The quantitative analysis method was adopted and the SPSS statistical tool was used to analyze the data using both descriptive and inferential statistics. Results have shown that several factors significantly affect consumer intention to use QR code-based payment namely performance expectancy, effort expectancy, hedonic motivation, habit, and trust. This study provides meaningful insight on the reasons why consumers used QR code-based payment.